KONSTRUKSI VEKTOR BINER UNTUK EKSPRESI GEN dip22 (YANG DIISOLASI DARI TEBU VARIETAS M 442-51) PADA TANAMAN - Wiwit Budi Widyasari; Sony Suhandono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Sugarcane is the principle plant for producing sugar in Indonesia. Water supply is one key element in the agronomy of sugarcane. Sugarcane is a high biomass crop which requires large amounts of water. Low yields of sugar observed in water stressed plants indicate that sugarcane is very sensititive to drought. A number of genes that respond to drought, salt, and cold stress at the trasnscriptional level have been reported. dip22 (drought inducible protein) protein isolated from drought resistance variety M 442-51 was predicted to be a protein regulator to water stress in sugarcane. Increasing of tolerance to water stress by over expression of dip22 genes in high yield sugarcane variety hopefully will maintain sugar production. The goal of this research was to construct a binary vector for dip22 gene expression in plant. dip22 gene from mutated PCR was cloned to pGEM®–T Easy and transformed to Escherichia coli strain DH5a. And then, these gene was isolated again from pGEM®–T Easy-dip22 (pGdip) plasmid using restriction enzymes NcoIand PmlI. pCAMBIA 1303 plasmid is an expression vector which has the constitutive promoter CaMV35S. Recombinant plasmid was transformed to Escherichia coli strain DH5a for plasmid propagation through DNA replication. Recombinant plasmid was isolated, and digested with NcoI and PmlI to examine the presence of dip22 gene in the pCAMBIA 1303 plasmid. The recombinant plasmid was transformed to A. tumefaciens strain LBA 4404. Plasmid isolated from A. tumefaciens was digested with Bst XI and Bst EII to examine the similarity between pCAMBIA 1303-dip22 (pCdip) from Escherichia coli and A. tumefaciens. The result by electrophoresis showed that both plasmids had the same size after digested. It was concluded that the transformed A. tumefaciens strain LBA 4404 bacteria has pCAMBIA 1303-dip22 (pCdip) plasmid indeed. Therefore, this construct of dip22 gene in binary vector can be used for improving drought tolerance in plant.